2015
DOI: 10.7860/jcdr/2015/8001.5586
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Ovarian Drilling in Women with Polycystic Ovary Syndrome

Abstract: Objective: To determine the effectiveness and safety of laparoscopic ovarian drilling (LOD) in inducing ovulation in women with polycystic ovary syndrome (PCOS) who failed to conceive after medical methods of ovulation induction. Materials and Methods:A retrospective study of all women who underwent LOD as a treatment for anovulatory infertility between January 2010 and December 2011 was conducted. Women diagnosed to have PCOS by the Rotterdam criteria were considered for the study. Those who had PCOS but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…An additional 15.7% of women conceived with the use of clomiphene citrate, making the total spontaneous PR 62.7%. Results from this study are comparable to Yanamandra and Gundabattula (2015) who reported 24.3% spontaneous pregnancies and additional 37.8% pregnancies after ovulation induction with clomiphene citrate in the 18-month follow-up period, and Felemban et al (2000) who reported 68% PR in the 18-month follow-up period.…”
Section: It Has Been Shown That the Presence Of Subserous Or Intraligamentarysupporting
confidence: 79%
See 2 more Smart Citations
“…An additional 15.7% of women conceived with the use of clomiphene citrate, making the total spontaneous PR 62.7%. Results from this study are comparable to Yanamandra and Gundabattula (2015) who reported 24.3% spontaneous pregnancies and additional 37.8% pregnancies after ovulation induction with clomiphene citrate in the 18-month follow-up period, and Felemban et al (2000) who reported 68% PR in the 18-month follow-up period.…”
Section: It Has Been Shown That the Presence Of Subserous Or Intraligamentarysupporting
confidence: 79%
“…Until a few years ago, endoscopic surgical procedures were considered a gold standard for infertility investigation as they are minimally invasive and serve as a diagnostic and therapeutic method at the same time (Yanamandra and Gundabattula, 2015). They can be used as a primary treatment of infertility as well as to enhance outcomes in IVF procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized trial comparing metformin and CC, where the primary outcome was live birth rate (LBR), Kar and Sanchita88 reported that the efficacy of metformin was similar to clomiphene in terms of LBR, and their combination gave the highest ovulation rate and LBR. Yanamandra and Gundabattula89 conducted a retrospective study of women who failed ovulation induction for primary infertility and hence underwent diagnostic laparoscopy and hysteroscopy followed by ovarian drilling. They showed an enhanced conception rate (around 50%) with laparoscopic ovarian drilling (LOD).…”
Section: Management Of Pcosmentioning
confidence: 99%
“…All ovarian drilling procedures result in reproductive endocrine changes [12,13]. It is not known which of these changes are the result of ovarian drilling and which are related to the surgery per se.…”
Section: Discussionmentioning
confidence: 99%